Turnover in local parasite populations temporarily favors host outcrossing over self‐fertilization during experimental evolution. Issue 13 (11th June 2018) - Lynch, Zachary R.; Penley, McKenna J.; Morran, Levi T.
Abstract: The ubiquity of outcrossing in plants and animals is difficult to explain given its costs relative to self‐fertilization. Despite these costs, exposure to changing environmental conditions can temporarily favor outcrossing over selfing. Therefore, recurring episodes of environmental change are predicted to favor the maintenance of outcrossing. Studies of host–parasite coevolution have provided strong support for this hypothesis. However, it is unclear whether multiple exposures to novel parasite genotypes in the absence of coevolution are sufficient to favor outcrossing. Using the nematode Caenorhabditis elegans and the bacterial parasite Serratia marcescens, we studied host responses to parasite turnover. We passaged several replicates of a host population that was well‐adapted to the S. marcescens strain Sm2170 with either Sm2170 or one of three novel S. marcescens strains, each derived from Sm2170, for 18 generations. We found that hosts exposed to novel parasites maintained higher outcrossing rates than hosts exposed to Sm2170. Nonetheless, host outcrossing rates declined over time against all but the most virulent novel parasite strain. Hosts exposed to the most virulent novel strain exhibited increased outcrossing rates for approximately 12 generations, but did not maintain elevated levels of outcrossing throughout the experiment. Thus, parasite turnover can transiently increase host outcrossing. These results suggest that recurring episodes of parasite turnover have the potential to favor the maintenance of host outcrossing. However, such maintenance may require frequent exposure to novel virulent parasites, rapid rates of parasite turnover, and substantial host gene flow. Abstract : Host–parasite coevolution has been well‐supported as a mechanism that can favor the maintenance of host outcrossing despite its inherent costs, but it is unclear whether recurring turnover in local parasite populations in the absence of coevolution could have similar effects. We subjected several replicate nematode populations to single parasite turnover events and passaged the populations for 18 generations. Hosts that were passaged with the most virulent novel strain exhibited the highest outcrossing rates and the most rapid adaptation, suggesting that recurring episodes of parasite turnover have the potential to favor the maintenance of host outcrossing.